A13 GUT MICROBIOTA MODULATES CGRP PRODUCTION BY DRG NEURONS IN FEMALE MICE. (21st February 2022) - Pujo, J; De Palma, G; Lu, J; Collins, S M; Bercik, P
Abstract: Background: Abdominal pain is a common complaint in patients with chronic gastrointestinal disorders. Accumulating evidence suggests that gut microbiota is an important determinant of gut function, including visceral sensitivity. Germ-free (GF) mice have been shown to display visceral hypersensitivity, which normalizes after colonization. Thus, gut microbiota is involved in the regulation of gut nociception but the underlying mechanisms remain poorly understood. Aims: To investigate the role of gut microbiota in abdominal pain. Methods: Method : Adult female and male conventionally raised (SPF) or GF mice were used. Their visceral sensitivity was assessed by visceromotor responses to colorectal distension, at baseline (vehicle: Tween 80 10%, Ethanol 10%, saline 80%) and after intracolonic administration of a TRPV1 agonist capsaicin (30 μg), or a mixture of G-protein coupled receptors agonists (GPCR: bradykinin, histamine and serotonin; 30 μg). Neuronal excitability of dorsal root ganglia (DRG) neurons was assessed by calcium imaging using a fluorescent probe Fluo-4 (1 mM) after stimulation with capsaicin (12.5 nM, 125 nM and 1250 nM) or GPCR agonists (0.3 μM, 3 μM and 30 μM). The neuronal production of substance P (SP) and calcitonin gene-related peptide (CGRP) in response to capsaicin (1250 nM) or GPCR agonists (30 μM) was measured by ELISA. Results: At baseline, GF male mice exhibited higher responses to colorectal distension compared to SPF males, while SPF and GF females displayed similar visceral sensitivity. In contrast, both intracolonic capsaicin and GPCR agonists increased visceral sensitivity in GF females compared to SPF females, while responses were comparable in male groups. DRG neuronal activation after stimulation with capsaicin or GPCR agonists was similar in SPF and GF mice of both sexes. While stimulated production of SP by DRG neurons was similar in SPF and GF mice, regardless of sex, the production of CGRP in response to GPCR agonists was higher in GF female than SPF female mice. Conclusions: Our data suggest that visceral sensitivity in vivo differs according to the gut microbiota status, sex and the activation of TRPV1 and GPCR pathways. At the level of DRG neurons, the absence of gut microbiota does not affect the neuronal activation or production of SP. However, GPCR agonists-stimulated release of CGRP is higher in GF female compared to SPF female mice. All together, our data demonstrate that the gut microbiota modulates visceral sensitivity by regulating the production of CGRP in the sensory neurons, especially in female mice. Further mechanistic studies are needed to investigate the role of gut microbiota in visceral sensitivity. Funding Agencies: CIHR